2015
DOI: 10.4238/2015.april.22.16
|View full text |Cite
|
Sign up to set email alerts
|

Association between MTHFR 677C/T polymorphism and psoriasis risk: a meta-analysis

Abstract: ABSTRACT. Previous studies investigating the association between methylenetetrahydrofolate reductase (MTHFR) 677C/T polymorphisms and psoriasis risk have reported inconsistent results. The present metaanalysis aimed to comprehensively evaluate the association between MTHFR 677C/T polymorphism and psoriasis risk. The studies regarding the association between MTHFR 677C/T polymorphism and psoriasis risk were retrieved from the PubMed, Embase, Web of Science, Chinese National Knowledge Infrastructure, and Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Fourteen rare mutations in the MTHFR gene associated with severe enzymatic deficiency and one common polymorphism C677T associated with a milder enzymatic deficiency have been identified, but only the MTHFR gene (677C>T) polymorphism, which causes an Ala-to-Val substitution, has been demonstrated to be associated with psoriasis. [ 63 64 ] The homozygous form of the MTHFR gene at nucleotide 677 (C677T) is prevalent in 10% of the population. The MTHFR genotype of T/T has been reported to reduce the homocysteine response to folic acid to a greater extent than C/C or C/T.…”
Section: Ethylenetetrahydrofolate R Edmentioning
confidence: 99%
“…Fourteen rare mutations in the MTHFR gene associated with severe enzymatic deficiency and one common polymorphism C677T associated with a milder enzymatic deficiency have been identified, but only the MTHFR gene (677C>T) polymorphism, which causes an Ala-to-Val substitution, has been demonstrated to be associated with psoriasis. [ 63 64 ] The homozygous form of the MTHFR gene at nucleotide 677 (C677T) is prevalent in 10% of the population. The MTHFR genotype of T/T has been reported to reduce the homocysteine response to folic acid to a greater extent than C/C or C/T.…”
Section: Ethylenetetrahydrofolate R Edmentioning
confidence: 99%
“…Changes in folate status have also been reported as a risk factor in some cases of psoriasis . MTHFR gene variation and differences in presentation of the disease in varying ethnicities or populations have led to discrepancies between studies, and there is little information available on the association between MTHFR polymorphisms and psoriasis vulgaris . Different studies have reported conflicting results, ranging from strong linkage to no association between MTHFR and psoriasis …”
Section: Introductionmentioning
confidence: 99%
“…10,11 MTHFR gene variation and differences in presentation of the disease in varying ethnicities or populations have led to discrepancies between studies, and there is little information available on the association between MTHFR polymorphisms and psoriasis vulgaris. 12 Different studies have reported conflicting results, ranging from strong linkage to no association between MTHFR and psoriasis. 9,[12][13][14] The aim of the current study was to explore and describe the effects on homocysteine levels of two single nucleotide polymorphisms (SNPs) in the folateassociated gene MTHFR, and to assess their distribution in psoriatic clinical parameters in a Turkish population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the MTHFR genotypes in psoriatic patients in Australia (n=310) did not differ from controls, the homocysteine level was found to be higher in 33 patients compared to that in controls 51 . Two meta-analyses carried out on the publications until 2014, which did not include any studies from our country, concluded that there was no relationship between psoriasis and MTHFR polymorphism 52,53 . In brief, both of the arguments stating that there was a different MTHFR polymorphism in patients with psoriasis than in healthy people and that there was a relationship between polymorphism and homocysteine are not conclusive findings.…”
mentioning
confidence: 99%